Mobile Computing Clouds Interactive Model and Algorithm Based On Multi-core Grids - Liu Lizhao; Zhu Shunzhi; Sun Zhonghai; Li Qi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Multi-core technology is the key technology of mobile cloud computing, with the boom development of cloud technology, the authors focus on the problem of how to make the target code computed by mobile cloud terminal multi-core compiler to use cloud multi-core system construction, to ensure synchronization of data cross-validation compilation, and propose the concept of end mobile cloud entity indirect synchronization and direct synchronization; use wave ormation energy conversion, give our a method to calculate indirect synchronization value and direct synchronization value according to the cross experience and cross time of compilation entity; construct function relative level algorithm with Hellinger distance,  and give an algorithm method of comprehensive synchronization value. Through experiment statistics and analysis, take threshold limit value as the average, self-synchronization value as deviation, the update function of indirect synchronization value is constructed; an inter-domain multi-core synchronization flow chart is given; then inter-domain compilation data synchronization update experiment is carried out with more than 3000 end mobile cloud multi-core compilation environment. Through the analysis of data compilation operation process and results, the synchronization algorithm is proved to be reasonable and effective. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3279